2019
DOI: 10.1088/1361-665x/aae5f0
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependent modelling of magnetorheological (MR) dampers using support vector regression

Abstract: In this study, a magnetorheological (MR) damper is experimentally characterized and investigations on the temperature developed during the operation of the damper, its effect on the damper hysteresis are carried out. The increase in temperature at higher input current consequently reduces the damper peak force and energy dissipation, thus altering its hysteretic behaviour. This hysteresis, with dependency on temperature, is modelled using a Gaussian kernel based support vector regression (SVR) model. Three met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…For a viscoelastic polymer matrix, changing temperature would affect the entanglements and sliding of the soft and hard segments that disperse among particles, and thus influence the formation and destruction of particle chains [23]. Therefore, it is necessary to investigate the influence of temperature on dynamic properties since engineering applications require a MRG to possess satisfactory performance under different temperatures [24]. Unfortunately, despite the significance of the temperature-dependent rheological behavior of MRGs, there is little relevant literature, to the best of our knowledge, and only a few publications discuss this in part [19,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For a viscoelastic polymer matrix, changing temperature would affect the entanglements and sliding of the soft and hard segments that disperse among particles, and thus influence the formation and destruction of particle chains [23]. Therefore, it is necessary to investigate the influence of temperature on dynamic properties since engineering applications require a MRG to possess satisfactory performance under different temperatures [24]. Unfortunately, despite the significance of the temperature-dependent rheological behavior of MRGs, there is little relevant literature, to the best of our knowledge, and only a few publications discuss this in part [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Priya et al carried out displacement-controlled experiments to investigate the nonlinear hysteretic behavior of a MRF damper under different currents. It was found that high current would lead to an increase in the temperature of the damper and a reduction in its damping force and energy dissipation [24]. Moreover, the Arrhenius equation was adopted by Rabbani et al to explore a model that could precisely reflect the relationship between the maximum shear yield stress of a MRF and temperature and magnetic field [25].…”
Section: Introductionmentioning
confidence: 99%
“…Struct. 29 (2020) 037001 (15pp) https://doi.org/10.1088/1361-665X/ab6ba5 6 Author to whom any correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is always a challenging task to establish an accurate MRD dynamic model due to strong nonlinear hysteresis [5]. Recent researches show the capability of artificial intelligence (AI)-based techniques in modeling the MRD dynamics by performing machine learning and data mining [6,7]. In [8], a new algorithm named establishing neuro-fuzzy system was proposed to identify the dynamic characteristics of smart dampers, and the effectiveness of the proposed algorithm was verified.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors such as Peng et al [42] reported a modeling and parametric study on MR dampers. Furthermore some authors considered the effect of temperature on performance and mathematical modeling of MR dampers [43].…”
Section: Introductionmentioning
confidence: 99%